Implementasi Nilai-Nilai Pendidikan Karakter Peduli Lingkungan Anak Usia Dini Pada Tayo The Little Bus Movie - Rahmawati, Siti; Muthohar, Sofa; Fatmawati, Nilal Muna (LPPM Institut Pendidikan Nusantara Global, 2025)
The purpose of this study is to analyze in depth the content of character education values, especially concern for the environment contained in the animated cartoon series